THE DEVELOPMENT OF LKPD PREDICT, OBSERVATION, EXPLANATION, ELABORATION, WRITE AND EVALUATION (POE2WE) ON COLLIGATIVE PROPERTIES OF SOLUTIONS MATERIALS - Ningsih, Siti Warda; M.Noer, Asmadi; Erviyenni, Erviyenni (Universitas Islam Sumatera Utara, 2022)
This research was conducted based on a needs analysis that showed that the LKPD used was still lacking to develop the level of thinking skills of students. The purpose of this study is to develop a Learner Activity Sheet (LKPD) model of Predict, Observation, Explanation, Elaboration, Write and Evaluation (POE2WE) in chemistry learning on the subject matter of colligative properties of solutions. This research uses the research and development (RD) method with a limited 4-D development model. The steps for developing this research are (1) Define, (2) Design and (3) Develop. The instruments used in this study were validation sheets and user response questionnaires. Based on the validation results to determine the quality of the LKPD of the POE2WE model on the material colligative properties of the solution, validity was obtained in the aspects of content feasibility, POE2WE characteristics, language, presentation and graphic successively by 95.83%, 95.83%, 95.02%, 93.75% and 87.55 with valid criteria. Valid student activity sheets were tested for user response by 20 students and 2 chemistry teachers and obtained consecutive scores of 93.075% and 96.65% with good criteria. Based on the results of data analysis, it can be concluded that the resulting POE2WE model LKPD is declared valid and can be used in chemistry learning class XII SMA / MA material colligative properties of solutions to increase motivation and learning outcomes of students.